The loading path dependence of sand constitutive behaviour and its relationship with pressure dip in sand piles - Xiao, Qiong (2017)
The subject of granular materials attracts substantial interests from both the academic and engineering communities. Their ubiquitous existences in nature and industries certify their engineering importance. Although relatively straightforward at the particle scale, the collective response of granular materials could be very complicated. The pressure dip under a sand pile is one among many intriguing phenomena that granular materials exhibit. It refers to a small dip in pressure appearing underneath the sand pile with the peak pressure observed away from the centre of the sand pile. Since first reported by Hummel and Finnan (1920), this counter-intuitive phenomenon has attracted extensive research endeavours in the past few decades. It is now generally believed that the construction history is crucial to the pressure dip formation, but a quantitative explanation is not yet available.